Factors associated with chronic pain following breast reconstruction in Japanese women. Issue 5 (1st October 2020) - Shiraishi, Makoto; Sowa, Yoshihiro; Fujikawa, Kei; Kodama, Takuya; Okamoto, Akiko; Numajiri, Toshiaki; Taguchi, Tetsuya; Amaya, Fumimasa
Abstract: Chronic pain after breast surgery including breast reconstruction is a major concern for patients. However, the factors associated with chronic pain after breast surgery are uncertain in Japanese population. The aim of this study was to identify patient-specific and medical/surgical factors that predict chronic pain after breast surgery in Japanese patients. The subjects were 189 Japanese women undergoing breast surgery including tissue expander/implant (TE/implant), deep inferior epigastric perforator (DIEP) procedures and mastectomy only. Pain was assessed at one year postoperatively using a validated survey instrument: the Japanese version of the Short-Form McGill Pain Questionnaire (SF-MPQ-JV). A multiple linear regression model was used to examine the relationships of clinical factors with postoperative pain. Surveys were completed by 141 subjects. A younger age ( p  = .04) and bilateral procedures ( p  < .05) were both closely associated with the extent of increased postoperative pain at 1 year using the MPQ-Total pain rating. Compared to total mastectomy only, TE/implant procedures showed a significantly lower visual analog scale (VAS) ( p  = .04) and present pain index (PPI) ( p  = .03) scores. No factor related to chronic pain was also significantly related to the frequency of pain medication use postoperatively or the effect of social life of the patients. This study identified patients at risk for greater chronic pain after breast surgery. These findings will allow surgeons to improve patient comfort, reduce clinical morbidity and enhance patient satisfaction with their surgical outcome. Abbreviations : BMI: body mass index; CI: confidence interval; DIEP: deep inferior epigastric perforator flap; MPQ: McGill pain questionnaire; PPI: present pain index; SD: standard deviation; SF-MPQ-JV: Japanese version of the short-form McGill pain questionnaire; TE: tissue expander; VAS: visual analog scale